Podejście systemowe w ochronie informacji - Binsztok, Aleksander; Radziszewski, Tomasz (System approach in the information protection, 2006)
In this article the authors show the actual problems of the management of information protection in the space of virtual relations. In this field authors present such important issues as: necessity of implementation of the information security, - trial of the information protection, treatment connected with the information protection, - system treatment to the information protection, factors which condition the efficiency of information protection management system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1132, s. 49-58